PEMANFAATAN TEKNOLOGI SOLAR CELL SEBAGAI SUMBER ENERGI LISTRIK ALTERNATIF DI PANTI ASUHAN AL-HASANAH - Randis Randis; mahmud mahmud; Mohamad Isram; Lilik Damayanti; Asri Setiarini (Universitas Kadiri, 2019)
The need for electrical energy is a basic requirement besides the need for food and clothing, electrical energy is absolutely needed by the community to support all their daily activities. The purpose of carrying out community service activities is to provide an alternative source of electrical energy by utilizing solar cell panels which can be felt by the public in the form of DC voltage and AC voltage through an inverter device. The method applied in this service activity is to set a plan in the form of a system work diagram and then carry out the service activities in accordance with the work plan that was made previously. The results obtained are the availability of lighting facilities and electrical energy to start the pump so that it can meet the lighting needs and water needs of the orphanage.